Through restful waters and deep commotion: A study on burnout and health impairment of Italian seafarers from the JD-R model perspective. [version 1; peer review: 1 approved, 2 approved with reservations] - Lara Colombo; Lara Bertola; Margherita Zito; Clarissa Cricenti; Lorenzo Cena; Francesco Buscema (F1000Research, 2025)
Background The work experience of seafarers differs significantly from other land-based occupations due to several factors, particularly remoteness and the restricted work environment. This study seeks to examine the impact of burnout and health impairment in the maritime industry, using the Job Demand-Resources theory as a framework. Methods To investigate these phenomena, an online questionnaire was sent to 239 Italian seafarers (94.6% men, Mage = 39.44, SD = 12.8). We tested a mediated Structural Equation Model (SEM) aimed at predicting negative health outcomes. Results The results show that burnout plays a mediating role between job demands (such as workload and cognitive strain) and resources (such as social support and transformational leadership), influencing variables related to health impairment (such as sleep quality and physical well-being). Furthermore, the findings highlight the direct influence of occupational resources on seafarers’ health. Conclusions The discussion highlights the urgent need for more research in the field of organisational psychology in the maritime industry and the discrepancies between these findings, which are consistent with the existing maritime literature, and other studies that do not include seafarers in their sample groups.